2017
DOI: 10.4103/ijmr.ijmr_1441_16
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria-derived biomarkers for tuberculosis diagnosis

Abstract: Tuberculosis (TB) remains an escalating problem worldwide. The current diagnostic methods do not always guarantee reliable diagnosis. TB treatment is a time-consuming process that requires the use of several chemotherapeutics, to which mycobacteria are becoming increasingly resistant. This article focuses on the potential utility of biomarkers of mycobacterial origin with potential implications for TB diagnosis. Properly standardized indicators could become new diagnostic tools, improving and streamlining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…[ 28 , 29 ]. However, some of these biomarkers, including most pathogen-derived biomarkers, can identify specific infectious sources but do not generally differentiate between bacterial and viral infections, which is particularly important for antibiotic treatment decisions [ 30 , 31 ]. Therefore, we focus on host-derived protein-based biomarkers and gene expression signatures because they have recently been shown to be promising biomarkers for distinguishing between bacterial and viral infections.…”
Section: Assessing Infectious Disease Among Children: the Need For Immentioning
confidence: 99%
“…[ 28 , 29 ]. However, some of these biomarkers, including most pathogen-derived biomarkers, can identify specific infectious sources but do not generally differentiate between bacterial and viral infections, which is particularly important for antibiotic treatment decisions [ 30 , 31 ]. Therefore, we focus on host-derived protein-based biomarkers and gene expression signatures because they have recently been shown to be promising biomarkers for distinguishing between bacterial and viral infections.…”
Section: Assessing Infectious Disease Among Children: the Need For Immentioning
confidence: 99%
“…Using a biosensor platform to detect antibodies against MAs from patient serum improved MA detection (sensitivity 91.3% in TB and HIV positive patients) compared to ELISA [ 121 ]. Other techniques used to detect MAs are LC-MS and high-performance liquid chromatography, which are both expensive and require advanced user training to operate and interpret data, making them difficult to use in resource-poor settings [ 119 , 122 ]. MAs were detected in adult TB sputum by Shui et al The study demonstrated a sensitivity of 94% and specificity of 93% in discriminating between TB cases and controls [ 74 ].…”
Section: The Role Of “Omics” In Tb Diagnostic Developmentmentioning
confidence: 99%
“…MTB antigens contain the antigen 85, early secretory antigenic target-6 (ESAT-6), MPT64, CFP-10 and 19 kDa lipoprotein; among these, the ESAT-6 antigen secreted by the T cell is considered the specific diagnostic biomarker of active TB owing to its superior immunogenicity in MTB. , Moreover, ESAT-6 is encoded by Rv3875 genes in the RD-1 region of MTB and is absent in the nonvirulent TB vaccine Bacillus Calmette–Guerin . The diagnostic sensitivity of the interferon-gamma (IFN-γ) enzyme-linked immunospot assay to ESAT-6 antigen exceeded 90% but did not respond in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%